2011
DOI: 10.1016/j.ejcts.2011.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Realignment of the ventricular septum using partial direct closure of the ventricular septal defect in Tetralogy of Fallot

Abstract: Partial direct closure of the VSD corrects the primary defect in TOF, that is, the malalignment of the septum. It results in a straight, wide open left ventricular outflow tract and brings better support to the aortic root.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…13 As studies have demonstrated significant morbidity, increased mortality and late re-operation rates for infants who undergo repair before 3-6 months of age, shunting is still preferred by many for symptomatic neonates and younger infants. 6,12,14,15 In 13 of our patients (10%), surgery was performed before 1 year of age and, the youngest patient was being 4.5 months old. We didn't find the age and weight at the time of surgery to be strongly correlated with mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 As studies have demonstrated significant morbidity, increased mortality and late re-operation rates for infants who undergo repair before 3-6 months of age, shunting is still preferred by many for symptomatic neonates and younger infants. 6,12,14,15 In 13 of our patients (10%), surgery was performed before 1 year of age and, the youngest patient was being 4.5 months old. We didn't find the age and weight at the time of surgery to be strongly correlated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…11 Many centres favour correction in early infancy for all patients, to avoid complications of shunting and any adverse effects of more prolonged cyanosis or right ventricular hypertrophy. 12 Total repair performed at an early age requires less muscle resection and a smaller right ventricular outflow tract patch, which lowers risk of of aneurysm, arrhythmia and right ventricular dysfunction. In their recent study, Egbe et al reported no mortality among patients under 3 months old after repair of TOF.…”
Section: Discussionmentioning
confidence: 99%
“…La reparación total realizada a una edad temprana requiere menos resección muscular y un parche transanular más peque ño, lo que disminuye el riesgo de aneurismas, arritmias o disfunción ventricular derecha. 3,4 Egbe et al 5 reportaron en un reciente estudio sobre una cohorte de 97 pacientes con edad media de 4,9 meses (rango: 1-9 meses) y 5,3 kg de peso medio (rango: 3,1-9,8 kg) una tasa de mortalidad del 0%. Sin embargo, la realización de reparación quirúrgica a una menor edad, tama ño y peso podía constituir un reto y tener una peor evolución hemodinámica, asociándose a mayor morbilidad 6 .…”
Section: Discussionunclassified
“…The technique presented by Soquet and colleagues 1 is not entirely new and shares concepts with other reports in various pathologic settings of malalignment of the conal septum. [2][3][4] Luciani and associates 2 used left-sided placement of the VSD patch to pull the conal septum out of the outflow tract into the plane of the ventricular septum. Fulton and coworkers 3 described the use of an intentionally small VSD patch to avoid bulging into the LVOT.…”
mentioning
confidence: 99%
“…Fulton and coworkers 3 described the use of an intentionally small VSD patch to avoid bulging into the LVOT. Till and associates 4 reported a modification of VSD closure in tetralogy of Fallot to realign the LVOT by using either direct or patch closure of the VSD. These approaches shift the conal septum to achieve a more homogeneous outflow tract.…”
mentioning
confidence: 99%